Pelaksanaan Keterampilan Vokasional dalam Menumbuhkan Kemandirian Santri di Pondok Pesantren Al-Istiqomah Petanahan Kebumen - Nandha Dewanda; Ngarifin Shidiq; Siti Lailiyah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to comprehensively describe the implementation of vocational skills in fostering student independence at Al-Istiqomah Islamic Boarding School, Petanahan, Kebumen. The research focuses on vocational concepts, implementation processes, contributions to student independence, and supporting and inhibiting factors. This study employed a descriptive qualitative approach with a field study design. Data were collected through participatory observation, in-depth interviews, and documentation, then analyzed using the Miles and Huberman interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that the vocational program is based on the independent curriculum philosophy known as “TEKWE” (Praktek Dewe), which integrates religious values with local-based independence. The program is implemented through three main business units: sewing, agriculture/livestock farming, and carpentry, conducted outside formal school and Qur’anic study hours. The implementation of vocational skills contributes significantly to the development of students’ intellectual, emotional, social, physical, and economic independence. The success of the program is supported by adequate Vocational Training Center (BLK) facilities and the active role of the Kyai as the primary motivator. However, challenges remain, including limited synchronization with the dense boarding school schedule and a marketing system that still depends on internal leadership networks. Overall, the integration of vocational skills effectively develops students who are spiritually grounded, economically competitive, and independent.